Relação matriz-subsidiária: a mudança do papel de subsidiária de mercado emergente pela geração de conhecimento tecnológico - Stolzmann, Klaus Peter (Universidade do Vale do Rio dos Sinos, 2018)
Although managers have moderate expectations about their subsidiaries' ability to contribute to the strategic and technological renewal of the entire multinational organization, a number of measures could be taken to enable the creation of new technologies in the subsidiaries. As the knowledge generation in a subsidiary is a subject that has not yet been deeply explored in the academic field, the proposal of this work is to bring some contribution in the process of technological knowledge generation as a factor to change the role of a Brazilian subsidiary belonging to a multinational from a developed country. Through a single case study, the data were collected in document analysis, in loco observation and interviews with several collaborators, among them engineers, managers, expatriates, foreigners and Brazilians. Afterwards, the data were triangulated with the content analysis technique. The results indicate the relevance of the technological knowledge generation by the subsidiary and recognized by the headquarter, to change its role in the MNC, represented by a graphic diagram of how such a process occurred. During the process analysis, we noticed some peculiarities in the present case, such as the great significance role of the inpatriate (employee of the subsidiary who spends a certain time in the headquarter and returns) which was less discussed in the literature and for this specific case, the customer role relevance in the process of technological knowledge generation in the subsidiary country, as well as confirming the great importance of the subsidiary manager's role and the moderator factors in this process. Finally, this work brings some practical contribution to managers of emerging-country subsidiaries who can evaluate their subsidiary's initiatives, such as the training of its employees in the headquarters or the search of new projects to serve local clients, to get the parent's attention and prepare to change its role within the MNC.
Keywords: Relação matriz-subsidiária; Geração de conhecimento tecnológico; Transferência de conhecimento; Multinacional em mercados emergentes; Iniciativa da subsidiária; Headquarter-subsidiary relationship; Technological knowledge generation; Knowledge transfer; Multinational companies in emerging markets; Subsidiary iniciative; ACCNPQ::Ciências Sociais Aplicadas::Administração